2017
DOI: 10.1002/2017jb014363
|View full text |Cite
|
Sign up to set email alerts
|

Electronic environments of ferrous iron in rhyolitic and basaltic glasses at high pressure

Abstract: The physical properties of silicate melts within Earth's mantle affect the chemical and thermal evolution of its interior. Chemistry and coordination environments affect such properties. We have measured the hyperfine parameters of iron‐bearing rhyolitic and basaltic glasses up to ~120 GPa and ~100 GPa, respectively, in a neon pressure medium using time domain synchrotron Mössbauer spectroscopy. The spectra for rhyolitic and basaltic glasses are well explained by three high‐spin Fe2+‐like sites with distinct q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 76 publications
(158 reference statements)
3
8
0
Order By: Relevance
“…Iron was interpreted to be predominantly in sixfold coordination in albite‐diopside glasses (Keppler, ), basalt glass (Bell & Mao, ), and a variety of Fe‐Ti glasses (Nolet et al, ) with optical absorption spectroscopy. Using time‐domain Mössbauer and optical absorption spectroscopy on reduced basaltic glass, Solomatova et al () found that less than 15–20% of ferrous iron is in fourfold coordination and the rest of iron is consistent with fivefold and/or sixfold coordination. Thus, although the proportions of the site environments depend on composition, the reported coordination environments also depend strongly on the experimental technique and method of analysis and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Iron was interpreted to be predominantly in sixfold coordination in albite‐diopside glasses (Keppler, ), basalt glass (Bell & Mao, ), and a variety of Fe‐Ti glasses (Nolet et al, ) with optical absorption spectroscopy. Using time‐domain Mössbauer and optical absorption spectroscopy on reduced basaltic glass, Solomatova et al () found that less than 15–20% of ferrous iron is in fourfold coordination and the rest of iron is consistent with fivefold and/or sixfold coordination. Thus, although the proportions of the site environments depend on composition, the reported coordination environments also depend strongly on the experimental technique and method of analysis and interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Although szomolnokite exists on the surface of Earth and likely on Mars, it is unknown if it exists at depth within either planet. Although it is also known that hydrated sulfates play important roles in the metal and hydrologic exchanges [29], FeCO 3 siderite [30], FeSiO 3 ferrosilite [27], basaltic and rhyolitic glasses [24], and FeSO 4 ·H 2 O szomolnokite (this study). For szomolnokite, we include Model 2 (where site 3 undergoes a high-to low-spin transition) and Model 3 (where a fifth low-spin site gradually increases its weight fraction over a broad range of pressures).…”
Section: Discussionmentioning
confidence: 78%
“…Although there is only one crystallographic site for iron in szomolnokite at ambient conditions [13][14][15], two Mössbauer sites are required to fit the data. As discussed in previous works on iron-bearing phases Minerals 2020, 10, 146 5 of 11 characterized by a single crystallographic site for ferrous iron, such as bridgmanite and (Mg,Fe)O ferropericlase [23][24][25][26], additional Fe 2+ -like sites in the data evaluation of Mössbauer spectra may arise from differences in the next nearest-neighbor environments. Atomic-specific probes like Mössbauer spectroscopy are therefore capable of resolving such local-environment characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations